(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Poverty is complex and multidimensional problem Poverty is a complex and multidimensional problem in Iraq. In spite of the multiple policies and programs that have been put in place for development and poverty eradication, what has been achieved is not up to the required level, due to the inadequacy of these plans and strategies that have been applied without examining the type and causes of poverty at the level of each governorate or region. This problem has been exacerbated by global changes, and its tendency to open up to the outside world, without having the means to preserve its economy. Physical poverty is no longer the only measure of poverty. A new poverty scale has been developed, through the Oxford Initiative for Human Development and Poverty. It includes five key dimensions to meet the priorities of post-2003 development plans: education, standard of living, basic services, food and health, employment. Each dimension has evidences and weights. The evidence shows that the causes of poverty in Iraq vary from one governorate to another, and that material poverty (income poverty) accounts for only 17% of the causes of poverty in Iraq. This means that it is possible to reduce poverty rates by focusing on indicators of intangible poverty, implementing economic and social programs, reviewing the priorities of government spending, and focusing on investing in basic public services and improving their type. The research has been divided into three sections. The first section deals with the theoretical framework of poverty problem. The second one dealt with the reality of poverty in Iraq after 2003 and its types. The third one dealt with the proposed ways of dealing with poverty in Iraq. The third topic dealt with the theoretical framework of the concept of poverty. The study reached a set of conclusions and recommendation that contribute to the diagnosis of the problem and provide appropriate solutions.